A monocentric prospective study investigating digital engagement among geriatric hospital patients - Julia Göbel; Anna Kordowski; Jennifer Kasper; Martin Willkomm; Christian Sina (BMC Geriatrics)
Abstract Background The aging of society drives a rising demand for geriatric healthcare due to increased care needs and extended hospital stays in old age. Despite strained social security systems, ensuring high-quality medical care requires innovative solutions. Digitalization could be one of them, however older people, who are less digitally active, may not fully recognize its benefits. This study aims to assess digital participation among geriatric hospital patients and their views on continuous vital sign monitoring using wearables. Methods The survey was conducted at the geriatric hospital “Krankenhaus Rotes Kreuz Lübeck – Geriatriezentrum” to assess the digital participation of higher frailty patients requiring increased care. The questioning occurred between February 13th and March 10th, 2023. The questionnaire included demographic questions, questions about digital participation and digital skills, opinions on continuous monitoring, and a reflection on the impact of the coronavirus pandemic on internet use. Results Of the 201 consecutively admitted patients, 52 were excluded from participation in the study based on the inclusion/exclusion criteria, mostly due to illness. Of the remaining 149 invited patients, 66 (44.2%) agreed to be interviewed, mostly females (76%) with an average age of 81.2 years (SD = 7.1). As a result, 68.2% of participants reported online activity, whereby females and those with low education or high age (p = 0.027) were offline more often. On average, 1–2 internet-enabled devices were used. Continuous vital sign monitoring was favoured by 32 participants and 61 expressed no concerns. Conclusion Our findings align with previous studies involving participants of comparable age, indicating comparable results, apart from disease-related participation restrictions. However, the significant proportion of patients who did not want to participate (55.7%) and the analysis of the reasons for nonparticipation suggest that the actual number of geriatric patients who do not engage online is higher. While this does not necessarily imply a complete rejection of digital products by this demographic, it highlights the need for greater emphasis on usability, feasibility, and clarification in future endeavors.